The effects of memantine on recovery, cognitive functions, and pain after propofol anesthesia - Emik,Ulku (2016)
Abstract Objectives: Postoperative cognitive dysfunction refers to the problems associated with thought and memory that are often experienced after major surgery. The aim of this study is to evaluate the effects of intraperitoneally administered memantine on recovery, cognitive functions, and pain after propofol anesthesia. Methods: The study was conducted in Gazi University Animal Research Laboratory, Ankara, Turkey in January 2012. Twenty-four adult female Wistar Albino rats weighing 170-270 g were educated for 300 s in the radial arm maze (RAM) over three days. Group P was administered 150 mg kg−1 of intraperitoneal (IP) propofol; Group M was given 1 mg kg−1 of IP memantine; and Group MP was given 1 mg kg−1 of IP memantine before being administered 150 mg kg−1 of IP propofol. The control group received only IP saline. RAM and hot plate values were obtained after recovery from the groups that received propofol anesthesia and 30 min after the administration of drugs in other two groups. Results: The duration of recovery for Group MP was significantly shorter than Group P (p < 0.001), and the number of entries and exits in the RAM by Group MP was significantly higher during the first hour when compared to Group P (p < 0.0001). Hot plate values, on the other hand, were found to be significantly increased in all groups when compared to the control values, aside from Group C (p < 0.0001). Conclusion: In this study, memantine provided shorter recovery times, better cognitive functions, and reduced postoperative pain. From this study, we find that memantine has beneficial effects on recovery, cognitive functions, and pain after propofol anesthesia.